2018
DOI: 10.48550/arxiv.1801.04048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phononic Weyl Nodal Straight Lines in High-Temperature Superconductor MgB$_2$

Qing Xie,
Jiangxu Li,
Min Liu
et al.

Abstract: Based on first-principles calculations, we predict that the superconducting MgB 2 with a AlB 2 -type centrosymmetric lattice host the so-called phononic topological Weyl nodal lines (PTWNLs) on its bulk phonon spectrum. These PTWNLs can be viewed as countless Weyl points (WPs) closely aligned along the straight lines in the −H-K-H direction within the three-dimensional Brillouin zone (BZ). Their topological non-trivial natures are confirmed by the calculated Berry curvature distributions on the planes perpendi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The concept of topology from the electronic bandstructure has been successfully extended to the vibrational bandstructure of materials [89][90][91][92][93]. In recent works, topologically protected band-crossings have been reported in the phonon spectrum of solid state crystals [41,[94][95][96][97]. Soon after the theoretical prediction of double-Weyl phonons in the phonon spectrum of transition-metal monosilicides MSi (M=Fe, Co, Mn, Re, Ru) [94], Miao et al [98] experimentally reported the first observation of double Weyl points in FeSi by means of inelastic x-ray scattering measurements.…”
Section: Topology Of Phonons In Triple-point Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of topology from the electronic bandstructure has been successfully extended to the vibrational bandstructure of materials [89][90][91][92][93]. In recent works, topologically protected band-crossings have been reported in the phonon spectrum of solid state crystals [41,[94][95][96][97]. Soon after the theoretical prediction of double-Weyl phonons in the phonon spectrum of transition-metal monosilicides MSi (M=Fe, Co, Mn, Re, Ru) [94], Miao et al [98] experimentally reported the first observation of double Weyl points in FeSi by means of inelastic x-ray scattering measurements.…”
Section: Topology Of Phonons In Triple-point Metalsmentioning
confidence: 99%
“…Recently, topologically protected Weyl nodal lines have been predicted in the phonon spectrum of bulk MgB 2 [97].…”
Section: Topology Of Phonons In Triple-point Metalsmentioning
confidence: 99%
“…Since the theoretical prediction and experimental realization of Weyl semimetal state in the TaAs class of compounds [1][2][3][4], Weyl materials including Weyl fermions [5][6][7][8][9][10][11][12], Weyl photonic crystal [13,14] and Weyl phononic crystal [15][16][17][18][19][20] with novel surface states have attracted significant interest recently. The spin-1/2 Weyl points (WPs) emerging in solids without time reversal symmetry or inversion symmetry are the twofold degenerated crossing points of two linearly dispersing bands in the three directions of momentum space [21,22].…”
mentioning
confidence: 99%
“…Therefore, all these four crossing points of PW1, PW2, PW3, and PW4 are phononic Weyl-like points. It needs to be emphasized that the general Weyl point is in the 3D conical shape [23], as already emphasized in many electronic Weyl semimetals and several phononic Weyl materials [56][57][58][59][60][61][62]. However, given the fact that it is not physically allowed for any 3D shape for graphene due to its single layer structure and the phononic band is spinless, it is reason- able to define these crossings as Weyl-like phonons.…”
mentioning
confidence: 99%
“…Moreover, it needs to be emphasized that for PW4 no edge states can be clearly observed because the PW4-induced topologically protected phononic edge states fully overlap with the edge projection from the phonon dispersions of the pristine graphene. In the third, in similarity to the nodal lines in 3D crystals which exhibits nontrivial drumhead-like surface states for BaSn 2 , Ca 3 P, TlTaSe 2 and TiSi, ZrSiS [63][64][65][66][67] and the phononic Weyl nodal line MgB 2 [60], the existence of PNL of the pristine graphene at 24.38 THz induces the straight-line edge states, simultaneously, with an arc-like going-downwards parabola in its frequencies upon the q momentum, as shown in Fig. 4(d).…”
mentioning
confidence: 99%